Implementing Emergency Power Supply for Lighting and Sound System for a Mosque based on light and Movement Sensors - Ulinuha, Agus; Wicaksana, Rizky Dian (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Emergency power supply is necessary for a mosque particularly when prayer is happening while power cuts. The important devices required to remain alive at this event are lighting and sound system. For this purpose, a battery is needed to supply the devices and the lighting and movement sensors that used to control the emergency power supply. The battery is powered by a solar photovoltaic (PV) panel. The power supply switching between main power and battery is regulated by Automatic Transfer Switch. A 20 Ah, 12 Volt battery supplied by 50 WP solar PV panel is used to back up the power for 6 W LED light and sound system. The system is implemented on the Mosque of Al-Bakri, Mojosongo, City of Surakarta. Research purpose of implementing this system is to solve the problem of power cuts during worship.Â This research used survey and measurement methods. In conclusion of implementing this system the prayer may continue even the electricity went out.